DC League of Super-pets - Lewman, David (Step into reading., 2022)
"Whenever the people ... and pets! ... of Metropolis are in danger, Krypto the Super-Dog flies in to save the day! Fans of the new hit film will find the DC League of Super-Pets powered up for action in this full-color Step into Reading Step 2 leveled reader that's perfect for helping readers ages 4 to 6 take flight!"--